2008
DOI: 10.1007/s10695-008-9273-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary protein levels on growth, feed utilization, protein retention efficiency and body composition of young Heteropneustes fossilis (Bloch)

Abstract: An 8-week growth trial was conducted to assess the effect of dietary protein on growth, feed utilization, protein retention efficiency, and body composition of young Heteropneustes fossilis (10.02 +/- 0.09 g; 9.93 +/- 0.07 cm). Isocaloric (4.15 kcal g(-1), GE) diets with varying levels of protein (25, 30, 35, 40, 45, and 50% of the diet) were fed near to satiation to triplicate groups of fish. Optimum dietary protein was determined by analyzing live weight gain (LWG%), feed conversion ratio (FCR), protein effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
61
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 81 publications
(55 reference statements)
12
61
0
1
Order By: Relevance
“…Several studies showed that whenever high levels of protein is supplied in the diet, the level of nutrient utilisation decreased, and feed consumption is reduced. The requirement of nutrients for optimum growth are always more than the requirement for optimal production (Siddiqui and Khan, 2009;Hossain et al, 2012). FCR was found to be the lowest at 45% protein level compared to all other dietary treatments.…”
Section: R Ramesh Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies showed that whenever high levels of protein is supplied in the diet, the level of nutrient utilisation decreased, and feed consumption is reduced. The requirement of nutrients for optimum growth are always more than the requirement for optimal production (Siddiqui and Khan, 2009;Hossain et al, 2012). FCR was found to be the lowest at 45% protein level compared to all other dietary treatments.…”
Section: R Ramesh Et Almentioning
confidence: 99%
“…Studies on protein requirements of carps have been undertaken by many workers using casein based synthetic diets (Mahanta et al, 2008;Ismat et al, 2013). Adequate amino acid levels required to maximise the growth of fish is supplied through optimum dietary protein levels (Siddiqui and Khan, 2009). Excess protein in the diet increases the production cost and can lead to pollution of pond environment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Any reduction in dietary protein level without affecting fish growth can substantially reduce the cost of fish feed (Fiogbé 1996;Kim et al 2003;Jamabo and Alfred-Ockiya 2008). For many fish species, there is an optimum requirement of dietary protein to supply adequate amino acids for maximizing growth (Siddiqui and Khan 2009). If too much protein is supplied in the diet, only part of it is used to make new protein for growth, and the remainder will be converted into energy, which results in increased feed cost and increased ammonia nitrogen excretion as an indicator of water pollution.…”
Section: Introductionmentioning
confidence: 99%
“…If too much protein is supplied in the diet, only part of it is used to make new protein for growth, and the remainder will be converted into energy, which results in increased feed cost and increased ammonia nitrogen excretion as an indicator of water pollution. Thus, from economical as well as environmental perspective, it is important that inclusion of the dietary protein should be optimized (Siddiqui and Khan 2009;Akpinar/et al 2011). Therefore, the aim of the present study was to estimate the optimum dietary protein level on growth performance and proximate composition in family selected strains of olive flounder (F-5 generation).…”
Section: Introductionmentioning
confidence: 99%